High Medicaid Nursing Homes: Organizational and Market Factors Associated With Financial Performance. (February 2019) - Weech-Maldonado, Robert; Lord, Justin; Pradhan, Rohit; Davlyatov, Ganisher; Dayama, Neeraj; Gupta, Shivani; Hearld, Larry
High Medicaid nursing homes (85% and higher of Medicaid residents) operate in resource-constrained environments. High Medicaid nursing homes (on average) have lower quality and poorer financial performance. However, there is significant variation in performance among high Medicaid nursing homes. The purpose of this study is to examine the organizational and market factors that may be associated with better financial performance among high Medicaid nursing homes. Data sources included Long-Term Care Focus (LTCFocus), Centers for Medicare and Medicaid Services' (CMS) Medicare Cost Reports, CMS Nursing Home Compare, and the Area Health Resource File (AHRF) for 2009-2015. There were approximately 1108 facilities with high Medicaid per year. The dependent variables are nursing homes operating and total margin. The independent variables included size, chain affiliation, occupancy rate, percent Medicare, market competition, and county socioeconomic status. Control variables included staffing variables, resident quality, for-profit status, acuity index, percent minorities in the facility, percent Medicaid residents, metropolitan area, and Medicare Advantage penetration. Data were analyzed using generalized estimating equations with state and year fixed effects. Results suggest that organizational and market slack resources are associated with performance differentials among high Medicaid nursing homes. Higher financial performing facilities are characterized as having nurse practitioners/physician assistants, more beds, higher occupancy rate, higher Medicare and Medicaid census, and being for-profit and located in less competitive markets. Higher levels of Registered Nurse (RN) skill mix result in lower financial performance in high Medicaid nursing homes. Policy and managerial implications of the study are discussed.